Religion and Religious Beliefs as Evolutionary Adaptations - Szocik, Konrad (Zygon, 2017)
Scholars employing an evolutionary approach to the study of religion and religious beliefs search for ultimate explanations of the origin, propagation, and persistence of religious beliefs. This quest often pairs in debate two opposing perspectives: the adaptationist and “by-product” explanations of religion and religious beliefs. The majority of scholars prefer the by-product approach, which is agnostic and even doubtful of the usefulness of religious beliefs. Despite this pervasive negativity, it seems unwarranted to deny the great usefulness of religious beliefs—particularly concerning their past utility. Instead, adaptationist explanations of religion and religious beliefs must be re-established as interesting and useful approaches to the study of religious beliefs.